Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper, 2011)
Lower-than-expected demand over the recent past has raised the lending capacity of the PRGT for the years 2012-14. Staff's latest projections suggest PRGT demand in 2011 could be about SDR 1.4 billion, up from SDR 1.2 billion in 2010. Assuming the 2009 LIC financing package is completed, these projections would be consistent with lending capacity of about SDR 2.1 billion per year from 2012-14, or SDR 1.5 billion per year through 2015. Most of the targeted loan resources under the 2009 package have now been secured, but additional pledges of about SDR 1 billion in loans are still needed. Fourteen members have pledged SDR 9.8 billion in new loan resources for the PRGT, compared to the target of SDR 10.8 billion. New borrowing agreements totaling SDR 9.5 billion have been signed with thirteen lenders. Eight of these agreements provide loan resources in SDRs, and seven creditors also participate in the voluntary encashment regime.